HIBAH LISAN TANAH KAUM KOTO LANSANO MENURUT HUKUM ADAT MINANGKABA - Albert Tanjung (Universitas Nasional, 2019)
The existence of tanah ulayat (communal land) as a right of possession over land in Indonesia is recognized by Law - Act No. 5/1960 about the Indonesian Basic Agrarian Law, contained in Article 3, supported by Law - 1945 Article 18 letter B paragraph (2). As long as they exist, hak ulayat (communal land rights) are recognized in the order of National Land Law. Therefore, it is also valid for hak ulayat of Indigenous Minangkabau society that still exist today. There are several kinds of hak ulayat according to the Customary Law of Minangkabau, one of them is hak ulayat kaum (clan communal land rights) or also called tanah kaum (clan communal land). Tanah kaum has become the object of research. Research method used is a normative juridical research which is descriptive. Data collection is conducted through literature study with secondary data and analyzed qualitatively. Tanah kaum is a high-inherited wealth which according to Minangkabau Customary Law, the ownership should not be transferred to another party except certain things. Tanah kaum can only be given to the another party with special rule called ganggam bauntuak (right of use) based on grant. Grants can be made either orally or written. From these results, it can be concluded that the grants were made either orally or written is legal under Customary Law of Minangkabau.